BIOAKUMULASI LOGAM BERAT Cd DAN Pb PADA API-API (Avicennia alba) DI DESA BAGAN DELI KECAMATAN MEDAN BELAWAN (Bioaccumulation of Heavy Metals Cd and Pb on Api-api (Avicennia alba) in Bagan Deli Village, District of Medan Belawan) - Gilang Pradifta S; Yunasfi Djayus; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Many activities by human and industry in Bagan Deli Village and along the Deli river could be caused the present of heavy metal in acuatiq environmental and could be harm to aquatic organism. The purpose of researching in to analyze the content of heavy metals Cadmium (Cd) and Plumbum (Pb) on roots, barks, leaves and knowing the ability of A. alba in accumulating heavy metals. The sample was located in Bagan Deli Village, District of Medan Belawan. The analysis of heavy metals Cd dan Pb was carried out in a Balai Riset dan Standarisasi Industri Medan, by using the metod Atomic Absorption Spectrophotometry (AAS). The results of this research indicated that the heavy metal content of Pb in the roots, barks, and leaves is larger more than Cd. The result of this research, based on the bioconcentration factor, the ability of A. alba in accumulate heavy metals Cd and Pb categorized low, the average value of BCF Pb was 21,38 and BCF Cd was 3,66. The results of chemical physics parameter in Bagan Deli Village stilled in the normal range. Concentrations of Cadmium (Cd) in the water column at each station in average 0,0013 mg/l and the concentration of lead metal (Pb) in the water column 0,15 mg/l. Concentrations of Cadmium (Cd) in the sediment column at each station in average 0,002 mg/kg and the concentration of lead metal (Pb) in the sediment column 11,38 mg/kg. These results indicated the concentration of heavy metal Cu and Pb in the water column had exceeded the quality standard, while concentrations of Cu and Pb in sediments had not exceeded the quality standard.Keywords : Avicennia alba, Heavy Metal, Cadmium (Cd), Plumbum (Pb), AASPENDAHULUANMeningkatnya industri memberikan dampak